Macro-Prudential Policies to Mitigate Financial System Vulnerabilities - Claessens, Stijn (IMF Working Papers; Working Paper ;, 2014)
Macro-prudential policies aimed at mitigating systemic financial risks have become part of the policy toolkit in many emerging markets and some advanced countries. Their effectiveness and efficacy are not well-known, however. Using panel data regressions, we analyze how changes in balance sheets of some 2,800 banks in 48 countries over 2000-2010 respond to specific macro-prudential policies. Controlling for endogeneity, we find that measures aimed at borrowers--caps on debt-to-income and loan-to-value ratios--and at financial institutions--limits on credit growth and foreign currency lending--are effective in reducing asset growth. Countercyclical buffers are little effective through the cycle, and some measures are even counterproductive during downswings, serving to aggravate declines, consistent with the ex-ante nature of macro-prudential tools.